High entropy alloy catalyst
By using hydrogen calcified to react with metal oxide in molten salt, the problems of high temperature equipment and high cost in the existing high entropy alloy production methods are solved, and efficient and low-cost high entropy alloy production is achieved.
Patent Information
- Application Number
- JP2025008356
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2042-09-05
AI Technical Summary
The existing high-entropy alloy production methods require large-scale equipment at high temperatures, use expensive pure metal raw materials, have a variety of process steps, pose a risk of pollution, and are expensive.
Hydrogen calcified (CaH2) is used to react with metal oxides in molten salts containing rubidium or alkaline earth metals, and a high-entropy alloy is generated through a single-step reaction, and reducing agents such as hydrogen calcified and metal calcium are used to reduce process temperature and cost.
It realizes low-cost and simple process production of high-entropy alloys, reduces equipment requirements and pollution risks, and improves production efficiency and product quality.
Smart Images

Figure 2025069957000004 
Figure 2025069957000005 
Figure 2025069957000006
Abstract
Description
[Technical field]
[0001] The present invention relates to methods for making high entropy alloys, methods for using high entropy alloys, high entropy alloy catalysts, and novel high entropy alloys. [Background technology]
[0002] In recent years, high entropy alloys (hereinafter referred to as HEAs) have been attracting attention as a new alloy material. HEAs are multi-component alloys with five or more components, in which various elements are randomly arranged in the crystal lattice, i.e., the entropy of the arrangement is high, and they are basically composed of a single-phase irregular solid solution. HEAs have the following characteristics: (a) stabilization of the mixed state due to a negative increase in the mixing entropy term in the Gibbs free energy equation, (b) diffusion retardation due to a complex microstructure, (c) high hardness and reduced temperature dependence of mechanical properties due to high lattice distortion caused by the size difference of the constituent atoms, and (d) improved corrosion resistance due to the combined effect (also called the cocktail effect) of the coexistence of multiple elements. HEAs have excellent corrosion and oxidation resistance, excellent friction resistance, and other factors, and are therefore being considered for use in various applications. For example, their main applications include shape memory alloys, which are used in various fields such as medical devices and structural materials, as well as in new application fields such as 3D metal printers, and as catalyst materials.
[0003] Methods for producing such high-entropy alloys include a physical method of mixing, melting and pulverizing raw materials, and a chemical method using a metal melt decomposition process. For example, Patent Document 1 discloses a physical method for producing a high-entropy alloy by a process of mixing and melting raw materials, an atomization process, a mixed powder preparation process, an additive manufacturing process, a pseudo-solution heat treatment process, and the like. Patent Document 2 discloses a mechanical alloying technique for obtaining a solid alloy by pulverizing element powders or pre-alloyed powders in a ball mill until a homogeneous alloy is formed.
[0004] As a chemical method utilizing molten metal decomposition, a precursor alloy of each element is prepared, melted by arc melting to mix the components, and a thin plate-shaped precursor is cut out from the solidified alloy and immersed in a metal bath consisting of a specific metal to obtain a porous metal (Patent Documents 3-4). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-114948 A [Patent Document 2] Special Publication No. 2022-530648 [Patent Document 3] JP 2020-125523 A [Patent Document 4] International Publication No. 2011 / 092909 Summary of the Invention [Problem to be solved by the invention]
[0006] In the physical method, the process of mixing and melting the raw materials usually requires melting and mixing the constituent metals at high temperatures (about 2000°C), so large-scale high-temperature resistant equipment such as a high-frequency melting furnace is required. In addition, expensive pure metals are used as raw materials, and there are many manufacturing steps, which increases the workload and costs, and there is a risk of impurities being mixed in at each step, such as the crushing step. And in the chemical method, there are problems such as using expensive pure metals as raw materials, going through a complicated process of selecting the metals to be used in each step taking into account the heat of mixing and melting point, and the number of manufacturing steps.
[0007] Such HEAs are expected to be used in a wide range of catalytic materials, and it is desirable to develop new high-entropy alloys to explore new applications for high-entropy alloys. The present invention has been made to solve the above problems, and aims to provide a method for producing a high-entropy alloy that can produce a high-entropy alloy simply and at low cost, and a method for using the high-entropy alloy. The present invention also provides a high-entropy alloy catalyst and a new high-entropy alloy. [Means for solving the problem]
[0008] The inventors discovered that high-entropy alloys can be obtained in a single-step reaction by heating and reducing the salts of each metal element or the oxide precursors of their hydrates in a molten salt containing an alkali metal or an alkaline earth metal using calcium hydride (CaH2), calcium (Ca), or the like as a reducing agent, and completed the present invention. Using this method, high-entropy alloy catalysts and novel high-entropy alloys were produced.
[0009] The present invention relates to a method for producing a high-entropy alloy as described in (1)-(5) below. (1) A method for producing a high entropy alloy, comprising the steps of: obtaining a mixed solution of salts of five or more metals selected from the group consisting of period 4-6 and group 3-12 transition metals, aluminum, silicon, and lanthanoids in the presence of a solvent; drying and heating the mixed solution to obtain an oxide precursor; and heating and reducing the oxide precursor, at least one reducing agent selected from calcium hydride, calcium, magnesium hydride, and magnesium, and a molten salt of an alkali metal salt or an alkaline earth metal salt in the presence of an inert gas to obtain a high entropy alloy. (2) A method for producing a high entropy alloy described in (1) above, wherein the step of obtaining the mixed liquid is a step of mixing the metal salt and a chelating agent in the presence of a solvent to obtain the mixed liquid. (3) A method for producing a high entropy alloy described in (1) above, wherein the step of obtaining the mixed liquid is a step of mixing a salt of the metal and an oxide of the metal (excluding the metal of the salt of the metal) in the presence of a solvent to obtain a mixed liquid. (4) The method for producing a high entropy alloy described in (1) above, wherein the metal is selected from Ni, Fe, Cr, Co, Al, Mn, Ti, V, Zr, Ir, Pd, Pt, Rh, Ru, Au, Ag, Y, Ga, Ln, Ce, Pr, Nd, and Sm. (5) A method for producing a high entropy alloy described in (2) above, wherein at least one of the selected five or more metals is a precious metal, and the step of obtaining the mixed liquid is a step of further mixing a calcium salt to obtain the mixed liquid.
[0010] The present invention also relates to methods for using the high entropy alloys described in (6) and (7) below, high entropy alloy catalysts described in (8) and (9) below, and a novel compound described in (10) below. (6) A method for using a high entropy alloy, comprising producing a high entropy alloy powder by the method for producing a high entropy alloy according to (2) above, and using the high entropy alloy as a catalyst for a hydrogenation reaction in a liquid phase. (7) A method for using a high entropy alloy according to (6) above, wherein the liquid phase hydrogenation reaction is a synthesis reaction of an amine by hydrogenation of a nitro group or an imine. (8) The atomic composition ratio is AlCoCrFeNiV, AlCoCrFeNi, CoFeNiTiCr, CoFeNiTiV, Al 0.2 Co 1.5 CrFeNi 1.5 Ti 0.5 , (Ti 0.5 Zr 0.5 )(Cr 0.25 Mn 0.25 Fe 0.25 Ni 0.25 2. A high-entropy alloy catalyst for liquid-phase hydrogenation reactions, comprising a high-entropy alloy represented by any one of the following formulas: (9) The high entropy alloy catalyst according to (8) above, wherein the liquid phase hydrogenation reaction is a synthesis reaction of an amine by hydrogenation of a nitro group or an imine. (10) The atomic composition ratio is CeMnFeCoNiZn, or (La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 Sm 0.2 )MnFeCoNiZn, or (Y 0.2 La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 )A high-entropy alloy represented by the formula Ga2Ni3. Effect of the Invention
[0011] According to the present invention, it is possible to provide a method for producing a high-entropy alloy simply and at low cost, a method for using the high-entropy alloy, a high-entropy alloy catalyst, and a novel high-entropy alloy. [Brief description of the drawings]
[0012] [Figure 1] 1 shows an X-ray diffraction pattern and a scanning electron microscope (SEM) image of the HEA powder of Example 1. [Diagram 2] 1 shows an X-ray diffraction pattern and an SEM image of the HEA powder of Example 2. [Diagram 3] 1 shows an X-ray diffraction pattern and an SEM image of the HEA powder of Example 3. [Figure 4] 1 shows the X-ray diffraction pattern and SEM image of the HEA powder of Example 4. [Diagram 5] 1 shows the X-ray diffraction pattern and SEM image of the HEA powder of Example 5. [Figure 6] 1 shows the X-ray diffraction pattern and SEM image of the HEA powder of Example 6. [Figure 7] 1 shows the X-ray diffraction pattern and SEM image of the HEA powder of Example 7. [Figure 8] 1 is an X-ray diffraction pattern of the HEA powder of Example 8. [Figure 9] FIG. 1 is an X-ray diffraction pattern of the HEA powder of Example 9. [Figure 10] 1 is an X-ray diffraction pattern of the HEA powder of Example 10. [Figure 11] 1 is an X-ray diffraction pattern of the HEA powder of Example 11. [Figure 12] 1 is an X-ray diffraction pattern of the HEA powder of Example 12. [Figure 13] 1 is an X-ray diffraction pattern of the HEA powder of Example 13. [Figure 14] 1 is an X-ray diffraction pattern of the HEA powder of Example 14. [Figure 15] 1 is an X-ray diffraction pattern of the HEA powder of Example 15. [Figure 16] 1 is a graph showing the change in p-nitrophenol concentration over time in a hydrogenation reaction using the HEA powder of Example 1 as a catalyst. [Figure 17] 1 is a graph showing the change in p-nitrophenol concentration over time in a hydrogenation reaction using the HEA powder of Example 2 as a catalyst. [Figure 18] 1 is a graph showing the change in p-nitrophenol concentration over time in a hydrogenation reaction using the HEA powder of Example 3 as a catalyst. [Figure 19] 1 is a graph showing the change in p-nitrophenol concentration over time in a hydrogenation reaction using the HEA powder of Example 4 as a catalyst. [Figure 20] 1 is a graph showing the change in p-nitrophenol concentration over time in a hydrogenation reaction using the HEA powder of Example 5 as a catalyst. [Figure 21] 1 is a graph showing the change in p-nitrophenol concentration over time in a hydrogenation reaction using the HEA powder of Example 6 as a catalyst. [Figure 22] 1 is a graph showing the change in p-nitrophenol concentration over time in a hydrogenation reaction using the HEA powder of Example 7 as a catalyst support. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The method for producing a high entropy alloy according to an embodiment of the present invention is a method for reducing the raw material, that is, the salt of each metal element or the oxide precursor of its hydrate, in a molten salt containing an alkali metal or an alkaline earth metal, using calcium hydride (CaH2) or calcium as a reducing agent, and a high entropy alloy is obtained in a single reaction. This method can produce a novel high entropy alloy. In this specification, when a numerical range is indicated, the upper and lower limits are included.
[0014] A high entropy alloy is a multi-component alloy with five or more components, which is essentially a single-phase disordered solid solution alloy, and whose mixed state is stabilized due to a negative increase in the entropy of mixing term in the Gibbs free energy equation. The stable phase formed in the equilibrium state is given when the Gibbs free energy (ΔG) is minimized. Thermodynamically, ΔG is given by ΔG=ΔH-TΔS, and as entropy (ΔS) increases, ΔG decreases. The entropy of mixing term of a random ideal solution is given by the following equation.
number
[0015] The method for producing a high-entropy alloy in this embodiment includes the steps of: obtaining a mixed liquid from five or more kinds of raw material metal salts in the presence of a solvent; drying and heating the mixed liquid to obtain an oxide precursor; and heating and reducing the oxide precursor, at least one reducing agent selected from CaH2, Ca, MgH2, and Mg, and a molten salt of an alkali metal salt or an alkaline earth metal salt in the presence of an inert gas to obtain a high-entropy alloy. The constituent elements of high entropy alloys are metals selected from the group consisting of transition metals in periods 4-6 and groups 3-12 of the periodic table, aluminum, silicon, and lanthanoids. Although aluminum and silicon are not transition metals, they are common to the above transition metals in that they can be constituent elements that form high entropy alloys (solid solutions or intermetallic compounds). In addition, although silicon is strictly speaking a nonmetal, it is included in the metals in this specification because it has a common property with the above transition metals and aluminum of forming alloys (solid solutions or intermetallic compounds) with other metal elements. For example, nickel (Ni), iron (Fe), chromium (Cr), cobalt (Co), aluminum (Al), manganese (Mn), titanium (Ti), vanadium (V), zirconium (Zr), platinum (Pt), ruthenium (Ru), rhodium (Rh), gold (Au), iridium (Ir), Y (yttrium), gallium (Ga), lanthanum (Ln), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), etc. are selected. The number of elements to be selected is not limited to an upper limit as long as it is 5 or more, but if the number is large, it becomes difficult to dissolve in the process of obtaining a mixed liquid, so that about 5 to 10 types are preferable. In addition, each constituent element may be up to 35 atomic % (mol %).
[0016] The present embodiment is characterized in that the above-mentioned metal salts or hydrates thereof are used as raw materials. In the conventional production of high entropy alloys, expensive pure metals are used as raw materials, but the raw metal salts and hydrates thereof are easily available and inexpensive, so that the cost can be reduced.
[0017] Metal salts include inorganic salts such as nitrates, sulfates, carbonates, phosphates, and chlorides of these metals, as well as organic salts such as alkoxides, acetates, and oxalates. In the case of inorganic salts, many nitrates or chlorides are soluble and inexpensively available, making them suitable. For example, when the raw metal is aluminum, there are hydrates of nitrates such as Al(NO3)3·9H3O, when it is cobalt, there are hydrates of nitrates such as Co(NO3)3·6H2O, when it is chromium, there are hydrates of Cr(NO3)3·9H2O, when it is iron, there are hydrates of Fe(NO3)3·9H2O, when it is nickel, and there are hydrates of Ni(NO3)2·6H2O. In addition, when it is vanadium or rhodium, it is preferable to use chlorides such as VCl3 and RhCl3, which are inexpensively available. In addition, metal alkoxides are preferably used for Ti and Si because they are available soluble compounds. Metal alkoxides are salts that are often used in the sol-gel method. Metal alkoxides may also be used for Al. The above salts may be hydrates. Any available salt of a soluble compound will suffice.
[0018] Then, the metal salt or its hydrate is mixed with the chelating agent in the presence of a solvent to obtain a mixed solution. The solvent can be ion-exchanged water, distilled water, glycerin, alcohol (especially ethanol), glycol (especially ethylene glycol, propylene glycol), standard organic solvents (THF, acetone, toluene), etc. Among these, distilled water and ethanol are preferable because they are easy to handle and inexpensive to obtain. Chelating agents are organic compounds that form chelate complexes with metal ions in a solution. Standard, highly safe agents include ethylenediaminetetraacetic acid, citric acid, phytic acid, and gluconic acid. Using chelating agents, it is possible to obtain uniform composite metal oxide powders using the sol-gel complex polymerization method. The number of moles of the chelating agent should be 1 to 1.5 times the total number of moles of the multiple metals.
[0019] On the other hand, when the number of constituent elements of an alloy is large (for example, 6 or 7 types or more), it may be difficult to obtain a uniform solution in which all metals are dissolved, as some raw materials are insoluble in solvents such as water or alcohol. In that case, it is recommended to prepare a suspension in which fine oxide powder is suspended instead of salt for some metals (preferably one type) (impregnation method). In this case, a chelating agent is not necessary, but it is recommended to use a chelating agent when, for example, the amount of oxide is small and it is difficult to prepare a uniform suspension. The use of a chelating agent has the effect of obtaining a precursor in which the metal is uniformly dispersed. In addition, it is recommended to use SiO2, TiO2, CeO2, etc. as the oxide powder, because the target is an element with limited soluble compounds available.
[0020] The mixed liquid is then dried and heated to obtain an oxide precursor. Heating may be performed in one step or multiple steps. For example, it is preferable to perform pre-calcination at a low temperature, followed by uniformly grinding and mixing the calcined sample in a mortar or the like using a pestle, and then performing main calcination at a high temperature, since this produces an oxide precursor in which elements are uniformly dispersed. The heating temperature is generally 300-800° C., but 400-600° C. is preferred because impurities other than metal elements (such as chelating agents) can be removed by combustion, or an oxide precursor with uniformly dispersed metal elements can be obtained. The heating time depends on the heating temperature, but is preferably about 0.5-10 hours, and more preferably about 3-6 hours.
[0021] Then, the oxide precursor, the reducing agent, and the molten salt source are mixed, and reduced by heating in the presence of an inert gas (nitrogen, argon, helium, etc.), to obtain HEA powder. After reduction, the product can be washed to remove impurities (LiCl, CaCl2, CaH2, CaO, etc.). The heating temperature during reduction varies depending on the type of molten salt, but must be equal to or higher than the melting temperature, and is generally 300-1000°C, preferably 550-800°C. Alternatively, the molten salt source may be heated first, and the oxide precursor and reducing agent may be added in a molten state, or the molten salt source and the oxide precursor or reducing agent may be mixed and heated, and the remaining reducing agent or oxide precursor may be added. In the case of a mixed molten salt, the melting point is lower than that of a single molten salt, so that it dissolves even at a temperature of, for example, less than 600°C. The molten salt acts as a solvent, and the oxide precursor is reduced by a reducing agent in the molten salt. By the molten salt reduction method, HEA powder can be obtained under mild conditions at a low temperature compared to the above-mentioned physical method (about 2000°C). The oxide precursor is alloyed immediately after reduction by the molten salt reduction method, and becomes a fine-particle alloy powder having a large specific surface area by passing through a metallic state. The heating time depends on the heating temperature, but is about 0.5 to 10 hours, preferably about 3 to 6 hours. If the heating temperature is low (for example, about 550°C), the heating time needs to be long (for example, about 10 hours), but if the heating temperature is high (for example, about 700 to 800°C), the heating time can be shortened (for example, about 2 hours).
[0022] The reducing agent may be calcium hydride, metallic calcium, magnesium hydride, metallic magnesium, or the like. These reducing agents exhibit a strong reducing action in the molten salt. The reducing agent may be used alone or in combination. When using a plurality of reducing agents, they may be mixed in advance or added separately when mixing the oxide precursor and the molten salt. In particular, CaH2 is preferred because it is a stable powder under room temperature and atmospheric conditions and can be handled relatively safely. When using CaH2 as a reducing agent, CaH2 is used in an amount equal to or greater than the number of moles of oxygen contained in the oxide precursor, utilizing the fact that CaH2 reacts with oxygen contained in the oxide precursor to form CaO. Preferably, the reducing agent is used in an amount of 0.1-4 times, preferably 1-2 times, the weight ratio of the oxide precursor.
[0023] The molten salt may be an alkali metal halide, an alkaline earth metal halide, or a mixture thereof. The alkali metal halide may be LiF, NaF, KF, RbF, CsF, LiCl, NaCl, KCl, RbCl, CsCl, LiBr, NaBr, KBr, RbBr, CsBr, LiI, NaI, KI, RbI, CsI, or other compounds. The alkaline earth metal halide may be MgF2, CaF2, SrF2, BaF2, MgCl2, CaCl2, SrCl2, BaCl2, MgBr2, CaBr2, SrBr2, BaBr2, MgI2, CaI2, SrI2, BaI2, or other compounds.
[0024] The above compounds can be used alone or in combination of two or more. The combination of these compounds, the number of compounds to be combined, the mixing ratio, etc. are not limited, and can be appropriately selected according to whether they are stable and easy to handle in air or whether they are inexpensively available. In addition, halides of relatively base metals such as AlCl3 and ZnCl2 can also be used.
[0025] In particular, the molten salt used in this embodiment is preferably a single molten salt such as LiCl or CaCl2, a mixed molten salt of LiCl and KCl, or a mixed molten salt of LiCl and CaCl2. In addition, the mixed molten salt has a lower melting point than a single molten salt, so it can react at a low temperature. Therefore, when the temperature at which the alloy is formed is low (for example, when the raw material contains an oxide that is easily reduced, such as a transition metal oxide), it is preferable to use a mixed molten salt. For example, the melting point of a mixed molten salt of LiCl and CaCl2 is 470°C, so it can react even at a low temperature of about 550°C.
[0026] The HEA produced by the above method is a fine-particle alloy powder with a large specific surface area. As a shape memory alloy, such alloy powder is expected to be used in a variety of applications, including medical devices and structural materials, as well as materials for 3D metal printers and catalyst materials. For example, when used as a shape memory alloy or 3D metal printer, it is possible to manufacture materials and molds with complex shapes by taking advantage of the characteristic that the particles are very small. Furthermore, since this HEA has a large specific surface area, it can be used as a catalyst material, either as a catalyst itself or as a carrier. For example, AlCoCrFeNiV, CrMnFeCoNi, AlCoCrFeNi, CoFeNiTiCr, CoFeNiTiV, Al 0.2 Co 1.5 CrFeNi 1.5 Ti 0.5 HEA powders such as these are primarily used as structural materials that require high strength, corrosion resistance, heat resistance, etc., but CrMnFeCoNi is also used as a catalyst in the reaction (C) below, and these HEA powders can be used as catalysts for hydrogenation reactions in the liquid phase. These HEA powders themselves function as catalysts, but they can also be used as catalyst supports.
[0027] For example, an example of a hydrogenation reaction in a liquid phase is shown below. (A) Conversion of alkenes (double bonds) and alkynes (triple bonds) to alkanes (B) Deprotection of the benzyl group (a compound containing an alcohol and a protecting benzyl group is hydrogenated to remove the benzyl group and obtain an alcohol.) (C) Hydrogenation of a nitro group or imine to obtain an amine. (D) Dehalogenation reaction by hydrogenation of aromatic halides (E) Hydrogenation of aldehydes or ketones to produce alcohols or methylenes In addition, (Ti 0.5 Zr 0.5 )(Cr 0.25 Mn 0.25 Fe 0.25 Ni 0.25)2 can be used as a catalyst for liquid phase hydrogenation reactions by supporting metal hydrogenation catalysts such as Ni, Pd, or Pt as a catalyst support. The reason why this alloy itself does not function as a catalyst is thought to be as follows. This alloy contains Ti and Zr, but these elements are located on the left side of the periodic table, have strong interactions with oxygen, and are prone to forming oxide films. This means that the active transition metals of the constituent elements Cr, Mn, Fe, and Ni are unlikely to be exposed on the surface. In particular, in organic synthesis, the hydrogenation of the nitro group (C) is a common reaction with a wide range of applications. For example, there is the hydrogenation reaction from p-nitrophenol to p-aminophenol, and NaBH4, hydrogen gas, LiAlH4, etc. are used as reducing agents.
[0028] Furthermore, by the above method, CeMnFeCoNiZn, (La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 Sm 0.2 )MnFeCoNiZn, (Y 0.2 La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 Novel HEAs such as Ga2Ni3 can also be fabricated. These HEAs contain rare earth elements (Ce, Ln, Pr, Nd, Sm, Y) and are compatible with the above-mentioned (Ti 0.5 Zr 0.5 )(Cr 0.25 Mn 0.25 Fe 0.25 Ni 0.25 It has more basic metal properties than Ti. It also has a large specific surface area. Therefore, it can be used as a catalyst or a basic support. 0.5 Zr 0.5 )(Cr 0.25 Mn 0.25 Fe 0.25 Ni 0.25 )2, as well as CeMnFeCoNiZn, (La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 Sm 0.2)MnFeCoNiZn, (Y 0.2 La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 ) New HEAs such as Ga2Ni3 can be used as catalyst supports. In this case, because of their strong basic metal properties, they are suitable for use as supports containing basic metals. For example, by supporting a metal catalyst for hydrogenation such as Ni, in addition to the above-mentioned liquid phase hydrogenation reaction, it can be applied to the synthesis of hydrocarbons or oxygen-containing hydrocarbons by hydrogenation of carbon monoxide or carbon dioxide. For example, it can be applied to the synthesis of methane by hydrogenation of carbon monoxide.
[0029] Furthermore, the above method can also be used to prepare HEAs containing precious metals such as IrPdPtRhRu, IrRhRuCoNi, AuPdPtRhRu, IrNiPtRhCo, and RuRhPdAgIrPtAu. These HEA powders are used as electrode catalysts, and can be used, for example, as catalysts for the electrolysis of ammonia. These HEA powders themselves also function as catalysts. In addition, since precious metals (Ir, Pd, Pt, Rh, Ru, Au, etc.) are stable, they may not easily become oxides even when fired at about 500℃ in the molten salt reduction method. Therefore, to prepare HEAs containing precious metals, it is preferable to add an appropriate amount of calcium salts such as Ca(NO3)2, CaCl2, (CH3COO)2Ca (for example, Ca=30mol%) to the raw materials and fire them, which will give a composite oxide of CaO and the precious metal (or a compound in which the precious metal is dispersed in CaO), making it easier to obtain oxide precursor powder. In addition, the added Ca will be removed by washing with a cleaning solution such as an aqueous NH4Cl solution in the final process, so it will not remain in the alloy.
[0030] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. EXAMPLES
[0031] Example 1 Al(NO3)3·9H3O (Fuji Wako Pure Chemical Industries, Ltd., purity 99%), Co(NO3)3·6H2O (Fuji Wako Pure Chemical Industries, Ltd., purity 98%), Cr(NO3)3·9H2O (Nacalai Tesque, Inc., purity 98%), Fe(NO3)3·9H2O (Fuji Wako Pure Chemical Industries, Ltd., purity 99%), Ni(NO3)2·6H2O (Fuji Wako Pure Chemical Industries, Ltd., purity 99.9%), VCl3 (Merck, purity 97%), and citric acid (Fuji Wako Pure Chemical Industries, Ltd.) were dissolved in distilled water to a molar ratio of Al / Co / Cr / Fe / Ni / V / citric acid = 1 / 1 / 1 / 1 / 1 / 1 / 7.2, and evaporated to dryness on a hot plate. The mixture was then pre-baked at 250°C for 2 hours. The calcined sample was crushed and mixed in a mortar with a pestle, and the powder was made uniform in particle size, and then calcined again at 500°C for 2 hours to obtain an oxide precursor (AlCoCrFeNiV(Pre)). The obtained oxide precursor was mixed with CaH2 (manufactured by Nacalai Tesque, Inc.) and LiCl-CaCl2 (manufactured by Fuji Wako Pure Chemical Industries, Ltd., molar ratio 1:1) in a weight ratio of 2 / 6 / 3, and heated in a SUS tubular furnace (similar to other examples) in an argon atmosphere at 550°C (reduction temperature) for 10 hours to perform molten salt reduction. The mixed molten salt source of LiCl and CaCl2 was prepared by mixing in a mortar with a pestle. Finally, the product was washed with 0.1M NH4Cl aqueous solution and distilled water to remove impurities (LiCl, CaCl2, CaH2, CaO, etc.), and HEA powder AlCoCrFeNiV was obtained. In the following examples, unless otherwise noted, the HEA powder was produced in the same manner and under the same conditions as in Example 1. In addition, the same reagents were used for common compounds.
[0032] The X-ray diffraction pattern and SEM image of the HEA powder are shown in Figure 1. The X-ray diffraction pattern was measured using an X-ray diffractometer (Mini Flex 600, manufactured by Rigaku Corporation) under the following conditions. Conditions: X-ray source CuKα, output 40KV, 15mA The SEM images were measured using a scanning electron microscope (JSM-7800F, manufactured by JEOL Ltd.). As can be seen from Figure 1, a single BCC structure is confirmed, and it can be said to be a single-phase solid solution alloy. In addition, the SEM image confirmed a microstructure consisting of fine particles of 1-10 μm or less. The BET specific surface area was calculated by nitrogen adsorption experiments and found to be 33.4 m 2 / g. From this result, it can be said that the obtained HEA powder has a fine structure. In the nitrogen adsorption experiment, the sample was dried at 200°C for 30 minutes under an inert gas flow, and then the amount of nitrogen adsorbed was measured at liquid nitrogen temperature.
[0033] Example 2 Cr(NO3)3·9H2O, Mn(NO3)2·6H2O (Fuji Wako Pure Chemical Industries, Ltd.), Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, and citric acid were dissolved in distilled water to a molar ratio of Cr / Mn / Fe / Co / Ni / citric acid = 1 / 1 / 1 / 1 / 1 / 7.2, and evaporated to dryness on a hot plate. The mixture was then pre-calcined at 250°C for 2 hours. The calcined sample was crushed to make the particle size almost uniform, and then calcined again at 500°C for 2 hours to obtain an oxide precursor (CrMnFeCoNi(Pre)). The resulting oxide precursor was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and heated at 700°C for 2 hours in a nitrogen atmosphere to perform molten salt reduction. Finally, the impurities were removed by washing the product with 0.1 M NH4Cl aqueous solution and distilled water to obtain the HEA powder CrMnFeCoNi. Figure 2 shows the X-ray diffraction pattern and SEM image of the HEA powder. A single FCC structure was confirmed from Figure 2, which indicates that it is a single-phase solid solution alloy. The SEM image also confirmed a microstructure consisting of fine particles of 1-10 μm or less. The specific surface area was 12.1 m 2 / g. From this result, it can be said that the obtained HEA powder has a fine structure. The above X-ray diffraction pattern, SEM image, specific surface area, etc. were measured by the same method and conditions as in Example 1. This is also common to the following examples.
[0034] Example 3 Al(NO3)3·9H2O, Co(NO3)2·6H2O, Cr(NO3)3·9H2O, Fe(NO3)3·9H2O, Ni(NO3)2·6H2O, and citric acid were dissolved in distilled water in a molar ratio of Al / Co / Cr / Fe / Ni / citric acid = 1 / 1 / 1 / 1 / 1 / 7.2, and evaporated to dryness on a hot plate. The mixture was then pre-fired at 250°C for 2 hours. The fired sample was crushed to make the particle size almost uniform, and then fired again at 500°C for 2 hours to obtain an oxide precursor (AlCoCrFeNi(Pre)). The oxide precursor obtained was mixed with CaH2 and LiCl-CaCl2 in a molar ratio of 2 / 6 / 3, and heated at 550°C for 10 hours in an argon atmosphere to perform molten salt reduction. Finally, the impurities were removed by washing the product with 0.1 M NH4Cl aqueous solution and distilled water to obtain the HEA powder AlCoCrFeNi. Figure 3 shows the X-ray diffraction pattern and SEM image of the HEA powder. A single BCC structure was confirmed from Figure 3, and it can be said to be a single-phase solid solution alloy. The SEM image also confirmed a microstructure consisting of fine particles of 1-10 μm or less. The specific surface area was 67.5 m 2 From this result, it can be said that the obtained HEA powder has a fine structure.
[0035] (Examples 4-5) Co(NO3)2·6H2O, Fe(NO3)3·9H2O, Ni(NO3)2·6H2O, [(CH3)2CHO]4Ti] (Fuji Wako Pure Chemical Industries, Ltd.), Cr(NO3)3·9H2O, VCl3, and citric acid were dissolved in ethanol on a hot plate to a molar ratio of Co / Fe / Ni / Ti / Cr or V / citric acid = 1 / 1 / 1 / 1 / 1 / 6, and evaporated to dryness in a dryer at 65°C. The mixture was then calcined at 250°C for 2 hours. The calcined sample was crushed to make the particle size almost uniform, and then calcined again at 500°C for 2 hours to obtain the oxide precursor (CoFeNiTiCr(Pre) or CoFeNiTiV(Pre)). The obtained oxide precursor was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and heated at 800°C for 2 hours in a nitrogen atmosphere to perform molten salt reduction. Finally, the product was washed with 0.1 M NH4Cl aqueous solution and distilled water to remove impurities, obtaining HEA powder CoFeNiTiCr (Example 4) and HEA powder CoFeNiTiV (Example 5).
[0036] Figures 4-5 show the X-ray diffraction pattern and SEM image of the HEA powder. In Example 4, a single FCC structure was confirmed from Figure 4, and it can be said to be a single-phase solid solution alloy. In addition, the SEM image confirmed a microstructure consisting of fine particles of 1-10 μm or less. The specific surface area was 23.1 m 2 / g. From this result, it can be said that the obtained HEA powder has a fine structure. Furthermore, in Example 5, a single FCC structure was confirmed from FIG. 5, and it can be said to be a single-phase solid solution alloy. Also, from the SEM image, a fine structure consisting of fine particles of 1-10 μm or less was confirmed. The specific surface area was 22.1 m 2 From this result, it can be said that the obtained HEA powder has a fine structure.
[0037] Example 6 Al(NO3)3·9H2O, Co(NO3)2·6H2O, Cr(NO3)3·9H2O, Fe(NO3)3·9H2O, Ni(NO3)2·6H2O, TiCl4, and citric acid were dissolved in distilled water to a molar ratio of Al / Co / Cr / Fe / Ni / Ti / citric acid = 0.2 / 1.5 / 1 / 1 / 1.5 / 0.5 / 7.2, and the solution was evaporated to dryness on a hot plate. It was then pre-calcined at 250°C for 2 hours. The calcined sample was crushed to make the particle size almost uniform, and then calcined again at 500°C for 2 hours to obtain the oxide precursor (Al 0.2 Co 1.5 CrFeNi 1.5 Ti 0.5 The oxide precursor obtained was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and then heated at 600°C for 2 hours under a nitrogen atmosphere for molten salt reduction. Finally, the product was washed with a 0.1M aqueous solution of NH4Cl and distilled water to remove impurities, and the HEA powder Al was obtained. 0.2 Co 1.5 CrFeNi 1.5 Ti 0.5 In addition, when the reduction temperature was set to 800°C (heating time was 2 hours), the same results were obtained for the HEA powder Al. 0.2 Co 1.5 CrFeNi 1.5 Ti 0.5 obtained. Figure 6 shows the X-ray diffraction pattern and SEM image of the HEA powder. From Figure 6, a single FCC structure was confirmed even at reduction temperatures of 600°C (Figure 6(A)) and 800°C (Figure 6(B)), and it can be said to be a single-phase solid solution alloy. In addition, from the SEM image, a microstructure consisting of fine particles of 1-10 μm or less was confirmed. The specific surface area was 91.7 m 2 / g(600℃), 13.6m 2 / g (800°C). From this result, it can be said that the obtained HEA powder has a fine structure.
[0038] Example 7 TiO2 (Sakai Chemical Industry Co., Ltd.), ZrO(NO3)2·2H2O (Fuji Wako Pure Chemical Industries Co., Ltd.), Cr(NO3)3·9H2O, Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Ni(NO3)2·6H2O, and citric acid were dissolved in distilled water to a molar ratio of Ti / Zr / Cr / Mn / Fe / Ni / citric acid = 1 / 1 / 1 / 1 / 1 / 1 / 7.2, and the solution was evaporated to dryness on a hot plate. The sample was then pre-calcined at 250°C for 2 hours. The calcined sample was crushed to make the particle size almost uniform, and then calcined again at 500°C for 2 hours to obtain the oxide precursor ((Ti 0.5 Zr 0.5 )(Cr 0.25 Mn 0.25 Fe 0.25 Ni 0.25 The oxide precursor was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and then heated at 800°C for 2 hours in a nitrogen atmosphere for molten salt reduction. Finally, the product was washed with a 0.1M NH4Cl aqueous solution and distilled water to remove impurities, and the HEA powder (Ti 0.5 Zr 0.5 )(Cr 0.25 Mn 0.25 Fe 0.25 Ni 0.25 )2 (composition TiZrCrMnFeNi) was obtained. Figure 7 shows the X-ray diffraction pattern and SEM image of the HEA powder. From Figure 7, a hexagonal close-packed structure was confirmed, and it can be said that an intermetallic compound was formed. From the XRD measurement results, the (Ti 0.5 Zr 0.5 )(Cr 0.25 Mn 0.25 Fe 0.25 Ni 0.25 )2 has a hexagonal crystal structure similar to TiCr2, and a single-phase intermetallic compound is formed that is stabilized by the contribution of the mixed entropy term. SEM images also confirmed a microstructure consisting of fine particles of 1-10 μm or less. The specific surface area is 22.5 m 2 From this result, it can be said that the obtained HEA powder has a fine structure.
[0039] Example 8 Ce(NO3)3·6H2O (Fuji Wako Pure Chemical Industries, Ltd.), Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O (Fuji Wako Pure Chemical Industries, Ltd.), and citric acid were dissolved in distilled water to a molar ratio of Ce / Mn / Fe / Co / Ni / Zn / citric acid = 1 / 1 / 1 / 1 / 1 / 1 / 7.2, and evaporated to dryness on a hot plate. Then, the sample was pre-calcined at 250°C for 2 hours. The calcined sample was crushed to make the particle size almost uniform, and then calcined again at 500°C for 2 hours to obtain the oxide precursor (CeMnFeCoNiZn(Pre)). The obtained oxide precursor was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and then heated at 800 °C for 2 h under a nitrogen atmosphere for molten salt reduction. Finally, impurities were removed by washing the product with 0.1 M NH4Cl aqueous solution and distilled water to obtain the novel HEA powder CeMnFeCoNiZn. Figure 8 shows the X-ray diffraction pattern and SEM image of the HEA powder. From Figure 8, a single FCC structure was confirmed, which indicates that it is a single-phase solid solution alloy. The specific surface area is 51.2 m 2 From this result, it can be said that the obtained HEA powder has a fine structure.
[0040] Example 9 La(NO3)3·6H2O (Fuji Wako Pure Chemical Industries, Ltd.), Ce(NO3)3·6H2O, Pr(NO3)3·nH2O (Fuji Wako Pure Chemical Industries, Ltd.), Nd(NO3)3·6H2O (Fuji Wako Pure Chemical Industries, Ltd.), Sm(NO3)3·6H2O (Fuji Wako Pure Chemical Industries, Ltd.), Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, and citric acid were dissolved in distilled water in a molar ratio of La / Ce / Pr / Nd / Sm / Mn / Fe / Co / Ni / Zn / citric acid = 0.2 / 0.2 / 0.2 / 0.2 / 0.2 / 1 / 1 / 1 / 1 / 1 / 7.2, and the solution was evaporated to dryness on a hot plate. The sample was then calcined at 250°C for 2 hours. The calcined sample was crushed to make the particle size uniform, and then calcined again at 500°C for 2 hours to obtain the oxide precursor ((La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 Sm 0.2 The oxide precursor was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and then heated at 800 °C for 2 hours under a nitrogen atmosphere for molten salt reduction. Finally, the product was washed with 0.1 M NH4Cl aqueous solution and distilled water to remove impurities, and a new HEA powder (La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 Sm 0.2 )MnFeCoNiZn was obtained. Figure 9 shows the X-ray diffraction pattern and SEM image of the HEA powder. From Figure 9, a single FCC structure was confirmed, which indicates that it is a single-phase solid solution alloy. The specific surface area is 25.8 m 2 From this result, it can be said that the obtained HEA powder has a fine structure.
[0041] Example 10 Y(NO3)3·nH2O (Fuji Wako Pure Chemical Industries, Ltd.), La(NO3)3·6H2O, CeO2 (Merck), Pr(NO3)3·nH2O (Fuji Wako Pure Chemical Industries, Ltd.), Nd(NO3)3·6H2O, Ga(NO3)3·nH2O (Fuji Wako Pure Chemical Industries, Ltd.), Ni(NO3)2·6H2O, and citric acid were dissolved in distilled water to a molar ratio of Y / La / Ce / Pr / Nd / Ga / Ni / citric acid = 0.2 / 0.2 / 0.2 / 0.2 / 0.2 / 2 / 3 / 7.2, and the mixture was evaporated to dryness on a hot plate. It was then pre-calcined at 250°C for 2 hours. The calcined sample was crushed to make the particle size almost uniform, and then calcined again at 500°C for 2 hours to obtain the oxide precursor ((Y 0.2 La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 The oxide precursor was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and then heated at 600°C for 2 hours under an argon atmosphere for molten salt reduction. Finally, the product was washed with 0.1M NH4Cl aqueous solution and distilled water to remove impurities, and a new HEA powder (Y 0.2 La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 )Ga2Ni3 was obtained. Figure 10 shows the X-ray diffraction pattern and SEM image of the HEA powder. Figure 10 confirms that the powder has a hexagonal close-packed structure, indicating that an intermetallic compound has been formed. The specific surface area is 19.9 m 2 / g. From this result, it can be said that the obtained HEA powder has a fine structure. In addition, the Herman-Morgan symbol and space group number of LnGa2Ni3 (Ln = La, Ce, Pr, Nd) are P62m and 189, and the XRD measurement results show that the (Y 0.2 La 0.2 Ce 0.2 Pr 0.2 Nd 0.2 )Ga2Ni3 has a single-phase crystal structure with P62m and 189 similar to LnGa2Ni3, and a single-phase intermetallic compound stabilized by the contribution of the mixing entropy term is formed.
[0042] Example 11 IrCl3·nH2O (Tokyo Chemical Industry Co., Ltd.), (NH4)2PdCl4 (Fuji Wako Pure Chemical Industries, Ltd.), H2PtCl6·6H2O (Fuji Wako Pure Chemical Industries, Ltd.), RhCl3 (Tanaka Kikinzoku Kogyo Co., Ltd.), RuCl3·nH2O (Fuji Wako Pure Chemical Industries, Ltd.), Ca(NO3)2·4H2O (Fuji Wako Pure Chemical Industries, Ltd., 30 mol% added), and citric acid were dissolved in distilled water to a molar ratio of Ir / Pd / Pt / Rh / Ru / citric acid = 1 / 1 / 1 / 1 / 1 / 7.2, and evaporated to dryness on a hot plate. Then, the sample was pre-calcined at 250°C for 2 hours. The calcined sample was crushed to make the particle size almost uniform, and then calcined again at 500°C for 2 hours to obtain the oxide precursor (IrPdPtRhRu(Pre)). The obtained oxide precursor was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and then heated at 600°C for 2 hours under an argon atmosphere for molten salt reduction. Finally, the product was washed with 0.1M NH4Cl aqueous solution and distilled water to remove impurities, yielding the HEA powder IrPdPtRhRu. Figure 11 shows the X-ray diffraction pattern and SEM image of the HEA powder. From Figure 11, a single FCC structure was confirmed, which indicates that it is a single-phase solid solution alloy. The specific surface area is 32.6 m 2 From this result, it can be said that the obtained HEA powder has a fine structure.
[0043] Example 12 IrCl3·nH2O, RhCl3 (Tanaka Kikinzoku Kogyo Co., Ltd.), RuCl3·nH2O (Fuji Wako Pure Chemical Industries, Ltd.), Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Ca(NO3)2·4H2O, and citric acid were dissolved in distilled water to a molar ratio of Ir / Rh / Ru / Co / Ni / citric acid = 1 / 1 / 1 / 1 / 1 / 7.2, and evaporated to dryness on a hot plate. The mixture was then pre-fired at 250°C for 2 hours. The fired sample was crushed to make the particle size almost uniform, and then fired again at 500°C for 2 hours to obtain an oxide precursor (IrRhRuCoNi(Pre)). The oxide precursor obtained was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and heated at 600°C for 2 hours in an argon atmosphere to perform molten salt reduction. Finally, the product was washed with 0.1 M NH4Cl aqueous solution and distilled water to remove impurities, and the HEA powder IrRhRuCoNi was obtained. Figure 12 shows the X-ray diffraction pattern and SEM image of the HEA powder. From Figure 12, a single FCC structure was confirmed, which indicates that it is a single-phase solid solution alloy. The specific surface area is 69.9 m 2 From this result, it can be said that the obtained HEA powder has a fine structure.
[0044] Example 13 HAuCl4·4H2O (Fuji Wako Pure Chemical Industries, Ltd.), (NH4)2PdCl4 (Fuji Wako Pure Chemical Industries, Ltd.), H2PtCl6·6H2O (Fuji Wako Pure Chemical Industries, Ltd.), RhCl3, RuCl3·nH2O, Ca(NO3)2·4H2O, and citric acid were dissolved in distilled water to a molar ratio of Au / Pd / Pt / Rh / Ru / citric acid = 1 / 1 / 1 / 1 / 1 / 7.2, and evaporated to dryness on a hot plate. The mixture was then pre-calcined at 250°C for 2 hours. The calcined sample was crushed to make the particle size almost uniform, and then calcined again at 500°C for 2 hours to obtain an oxide precursor (AuPdPtRhRu(Pre)). The obtained oxide precursor was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and heated at 600°C for 2 hours in an argon atmosphere to perform molten salt reduction. Finally, the product was washed with 0.1 M NH4Cl aqueous solution and distilled water to remove impurities, and the HEA powder AuPdPtRhRu was obtained. Figure 13 shows the X-ray diffraction pattern and SEM image of the HEA powder. From Figure 13, a single FCC structure was confirmed, which indicates that it is a single-phase solid solution alloy. The specific surface area is 50.2 m 2 From this result, it can be said that the obtained HEA powder has a fine structure.
[0045] Example 14 IrCl3·nH2O, Ni(NO3)2·6H2O, H2PtCl6·6H2O, RhCl3·3H2O, Co(NO3)2·6H2O, Ca(NO3)2·4H2O, and citric acid were dissolved in distilled water to a molar ratio of Ir / Ni / Pt / Rh / Co = 1 / 1 / 1 / 1 / 1 / 7.2, and evaporated to dryness on a hot plate. The mixture was then pre-fired at 250°C for 2 hours. The fired sample was crushed to make the particle size almost uniform, and then fired again at 500°C for 2 hours to obtain an oxide precursor (IrNiPtRhCo(Pre)). The oxide precursor obtained was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and heated at 600°C for 2 hours in an argon atmosphere to perform molten salt reduction. Finally, the product was washed with 0.1 M NH4Cl aqueous solution and distilled water to remove impurities, and the HEA powder IrNiPtRhCo was obtained. Figure 14 shows the X-ray diffraction pattern and SEM image of the HEA powder. From Figure 14, a single FCC structure was confirmed, which indicates that it is a single-phase solid solution alloy. The specific surface area is 25.5 m 2 From this result, it can be said that the obtained HEA powder has a fine structure.
[0046] Example 15 RuCl3-nH2O, RhCl3·3H2O, (NH4)2PdCl4, AgNO3 (Fuji Wako Pure Chemical Industries, Ltd.), IrCl3·nH2O, H2PtCl6·6H2O, HAuCl4·4H2O, Ca(NO3)2·4H2O, and citric acid were dissolved in distilled water to a molar ratio of Ru / Rh / Pd / Ag / Ir / Pt / Au=1 / 1 / 1 / 1 / 1 / 1 / 1 / 7.2, and evaporated to dryness on a hot plate. The sample was then pre-calcined at 250°C for 2 hours. The calcined sample was crushed to make the particle size almost uniform, and then calcined again at 500°C for 2 hours to obtain the oxide precursor (RuRhPdAgIrPtAu(Pre)). The oxide precursor was mixed with CaH2 and LiCl in a molar ratio of 2 / 6 / 3, and then heated at 600°C for 2 hours under an argon atmosphere for molten salt reduction. Finally, the product was washed with 0.1M NH4Cl aqueous solution and distilled water to remove impurities, yielding the HEA powder RuRhPdAgIrPtAu. Figure 15 shows the X-ray diffraction pattern and SEM image of the HEA powder. From Figure 15, a single FCC structure was confirmed, which indicates that it is a single-phase solid solution alloy. The specific surface area is 34.2 m 2 From this result, it can be said that the obtained HEA powder has a fine structure.
[0047] Table 1 shows the results summarizing the HEA powders prepared in Examples 1-15 above. [Table 1] From the above results, it is possible to obtain oxide precursors of salts or hydrates of each metal element by a simple method of heating and reducing them in a molten salt containing an alkali metal or an alkaline earth metal using calcium hydride (CaH2) or calcium as a reducing agent, and to obtain oxide precursors with a specific surface area of approximately 10 m 2 / g and 20m 2 It was confirmed that the alloy powder obtained was fine particles of approximately 1-10 μm or less and had a large specific surface area of 10 μm or more / g. Thus, the HEA powder of this example can be applied to structural materials and 3D metal printers that require fine processing. It is also suitable as a catalyst material that requires a large specific surface area and fine particles. Below, an example is shown in which the HEA powder obtained in Examples 1-7 was used as a catalyst for the synthesis reaction of amines by hydrogenation of nitro groups.
[0048] (Example 16) The HEA powder obtained in Example 1-6 was used in the hydrogenation reaction of p-nitrophenol to p-aminophenol to evaluate the HEA catalytic activity. p-Nitrophenol (maximum absorption wavelength: 401 nm) is converted to p-aminophenol (maximum absorption wavelength: 303 nm) by the hydrogenation reaction. The hydrogenation reaction was started by adding HEA powder (100 mg), 1 mL of 14 mM p-nitrophenol solution, 1 mL of 0.42 M NaBH4 solution, and 7 mL of distilled water to a glass tube and heating it. The reaction temperature (heating temperature) was set within the range of about 20-60°C depending on each HEA powder. The above experimental method and conditions are common to all examples, but in Examples 1-3, the reaction was carried out at multiple reaction temperatures, and in Examples 4-6, the reaction was carried out at 50°C. The HEA powder should be added in an amount of 1-500 times, preferably 10-100 times, p-nitrophenol by weight. After the reaction was started, 100-500μL of the test solution was taken from the glass tube at regular intervals and diluted in a 5mL measuring flask (by adding distilled water), and then the absorbance at 300-500nm was measured using a UV-Vis spectrophotometer (Shimadzu Corporation, UV-1280) to measure the concentration changes of p-nitrophenol and p-aminophenol. The results are shown in Figures 16-21. Figures 16-21 correspond to Examples 1-6, respectively.
[0049] These results indicate that the hydrogenation reaction of p-nitrophenol proceeded with the HEA catalyst. In addition, the HEA powder obtained in Examples 1-3 showed an activity effect at any temperature, and the concentration decreased significantly as the temperature increased, confirming that the reaction rate improved. It was also found that almost all or most of the p-nitrophenol was converted to p-aminophenol in a short period of time, about 10-30 minutes. These results confirmed that the obtained HEA catalyst exhibited excellent liquid-phase hydrogenation activity. In heterogeneous catalytic reactions, the reaction proceeds on the surface of the catalyst. For this reason, it is preferable to use a catalyst with a high specific surface area. The results showed that the high specific surface area of the HEA catalyst obtained in this example works effectively in the hydrogenation reaction. In particular, the Al obtained by reduction at 600°C, which has the largest specific surface area, 0.2 Co 1.5 CrFeNi 1.5 Ti 0.5 The catalyst (Example 6) showed the fastest reaction rate (Figure 21). 0.2 Co 1.5 CrFeNi 1.5 Ti 0.5 It can be said that this is preferable. In addition, in the case of AlCoCrFeNi (Example 3, FIG. 18), almost the entire amount reacted within 3 minutes, so this can also be said to be preferable. In particular, in Example 3, good results were obtained even at a relatively low reaction temperature (38°C).
[0050] The HEA powder obtained in Example 7 was used as a Ni-supported catalyst carrying 10 wt % Ni, and the HEA catalytic activity was evaluated. The Ni-supported catalyst was prepared by the following method. The HEA powder ((Ti 0.5 Zr 0.5 )(Cr 0.25 Mn 0.25 Fe 0.25 Ni 0.25 )2) was suspended, and then Ni(NO3)2·6H2O was dissolved in it so that the weight ratio of HEA / Ni was 9 / 1, and the mixture was evaporated to dryness on a hot plate. It was then heated at 500℃ for 1 hour under argon flow to obtain a Ni-supported catalyst with 10wt% Ni supported.
[0051] The HEA catalytic activity of the Ni-supported catalyst (100 mg) and the HEA powder (100 mg) obtained in Example 7 was evaluated in the same manner and under the same conditions as those for the HEA powder obtained in Examples 1-6 (reaction temperature: 50°C). The results are shown in Figure 22. From these results, almost no catalytic activity was observed with the HEA powder alone, but good catalytic activity was confirmed in a short reaction time by using the Ni-supported catalyst.
[0052] (Example 17) The crystallite sizes of the HEA powders obtained in Examples 8 to 15 were calculated from the XRD measurement results using the Scherrer equation. The results are shown in Table 2. [Table 2]
[0053] From Table 2, it can be said that the HEA powder obtained in Examples 8-15 is an alloy powder of nano-sized particles. The HEA powder obtained in Examples 8-10 is also suitable as a catalyst material that requires a large specific surface area and nano-sized particles. For the HEA powder obtained in Examples 11-15, the calculation limit is around 3-5 nm, and the quantitative crystallite size cannot be clearly shown, but since a wide peak is observed in XRD, it is clear that crystallites smaller than 5 nm are formed. The HEA powder obtained in Examples 11-15 can be used as an electrode catalyst such as a catalyst for the electrolysis of ammonia. [Industrial Applicability]
[0054] This shape-memory alloy has potential applications in a variety of fields, including medical devices and structural materials, as well as new application areas such as 3D metal printers and use as a catalyst material.
Claims
1. The atomic composition ratio is AlCoCrFeNiV, AlCoCrFeNi, CoFeNiTiCr, CoFeNiTiV, Al 0.2 Co 1.5 CrFeNi 1.5 Ti 0.5 , (Ti 0.5 Zr 0.5 ) (Cr 0.25 Mn 0.25 Fe 0.25 Ni 0.25 ) 2 A high-entropy alloy catalyst for liquid-phase hydrogenation reactions, comprising a high-entropy alloy represented by any one of the following formulas:
2. The high entropy alloy catalyst according to claim 1 , wherein the liquid-phase hydrogenation reaction is a synthesis reaction of an amine by hydrogenation of a nitro group or an imine.
Citation Information
Patent Citations
Reduction catalyst comprising palladium-gold alloy
JP2012091109A
Alloy structure
JP2016029193A
Mixed powder for metal lamination molding
JP2020114948A
Porous metal
JP2020125523A
Mechanically alloyed powder raw materials
JP2022530648A